Influence of medium composition and physical factors on enhanced production of endoglucanase by locally isolated fungal strain in solid state fermentation - Abdullah, Roheena; Javed Peracha, Bakhtawar; Nisar, Kinza; Iqtedar, Mehwish; Kaleem, afshan; Iftikhar, Tehreema; Saleem, Faiza; Naz, Shagufta (Cellular and Molecular Biology, 2018)
Endoglucanase is one of the most important enzymes of the cellulase group. Endoglucanase are involved in the catalytic hydrolysis of cellulose and plays a pivotal role in different sectors like pharmaceutical, textile, detergent, and food processing as well as paper and pulp industry. With consumers getting more and more aware of environmental issues, industries find enzymes as a better option over other chemical catalysts. In the current research different thermophilic fungal strains were isolated from the different sources. Qualitative screening was carried out on the basis of cellulose hydrolysis zone. The quantitative screening was carried out employing solid state fermentation. The fungal culture, showing highest EG potential was selected identified and assigned the code Aspergillus fumigatus BBT2. Different fermentation media were evaluated and M 2 containing wheat bran gave maximum EG production. The maximal enzyme productivity was recorded in 72 hours, 40°C, pH 5, inoculum size 1.5ml, and moisture content (1:1). Glucose (1%) and peptone (1%) were optimized as best carbon and nitrogen sources, respectively.